Evaluation of Online Learning Program: Study at Buddhist Sunday School, Vihara Jakarta Dhammacakka Jaya Buddhist Sunday School - Sugianto, Sugianto (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This study aimed to evaluate the online learning program at Buddhist Sunday School, Vihara Jakarta Dhammacakka Jaya by using the CIPP model. The result of this study showed that: (1) the online learning program at Buddhist Sunday School, Vihara Jakarta Dhammacakka Jaya was organized by Buddhist Sunday School’s administrators so the teachers could teach Dhamma to the students even during the Covid-19 pandemic; (2) The teachers and students need equipment, such as laptops and the internet to connect with zoom; (3) The teacher used PowerPoint to deliver the material. The learning was carried out by various methods, such as lectures, stories, watching movies, and online games; and (4) The online learning outcomes, including the development of knowledge, attitudes, and skills. The assessment was carried out by observation or orally. From online learning, the students could be cheerful even during the Covid-19 pandemic, they also can apply the devotional teachings to their parents, but on the other hand, they used gadgets more.